Gender Inequality in Russian Agriculture: Problems and Prospects of Legal Regulation - SAPFIROVA, Apollinariya A.; VOLKOVA, Victoria V.; KHAKHALEVA, Elena V.; KARDANOVA, Irina V. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The purpose of the article is to identify and examine the issues of legal regulation in the field of gender inequality in branches of agriculture. In the study, the authors implemented the method of legal analysis and the formal-legal method. Main results: The differences in labor conditions for men and women are objectified by the nature of childbirth and the need to preserve life. In Russia, men’s labor is more cost-effective for employers than women’s labor as it is not always convenient for employers to provide women with benefits stipulated by law. The latest developments by the Russian Ministry of Labor make provisions for an increased number of professions that women will be allowed to pursue. Numerous professions that women are currently prohibited from will soon become available to them. Conclusions: Having analyzed the provisions of Russian labor law, the authors have come to the main conclusion that not only is it necessary to review certain advantages given to women but also that there are certain discriminatory aspects against men (this refers to advantages for women working in rural areas). The conducted study will foster not only the efficient allocation of duties among workers by the employer but also justified labor differentiation for men and women, thus eliminating possible gender discrimination.